Sakti merah putih / Nur Zafira Zainol - Zainol, Nur Zafira (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
The goal of this study is to suggest a thorough rebranding for Komik-M products. The client's business is well-known for producing comic book-related products. 'Komik-M,' which was formed by Tuan Wan Zuhairi in Kuala Lumpur early in 2008, has been a major player in the book and comics industry, providing a vast collection with a strong foundation in Malay culture. Although the business has prospered in the print sector, there is a clear void in the exciting field of 2D animation, which offers room for expansion. It is advised that the business strategically enter the 2D animation market in order to improve its services. This change will not only draw in more readers, but it will also give the engrossing folktale stories included in the current comic books new life. To bring these stories to life on animated screens, it will be essential to work with experienced animators and make technological investments in animation. Moreover, marketing and revenue creation may benefit from broadening the product line by adding animated content. Through the integration of animated content into commercials, corporate presentations, and goods, 'Komik-M' can establish a multi-channel presence, hence increasing brand awareness. I recently used this method for my product and saw a significant spike in sales and engagement. Because animated content can be easily adapted to a variety of media, it can reach a larger audience. In conclusion, the incorporation of 2D animation into 'Komik-M's' product portfolio not only answers the current hole in their offers but also matches with contemporary consumer desires. This calculated action will set the business up for success by attracting a wide range of customers and guaranteeing long-term growth.